The prevalence of human papillomavirus in the oropharynx in healthy individuals in a Brazilian population - do Sacramento, P. R.; Babeto, E.; Colombo, J.; Ruback, MJC; Bonilha, J. L.; Fernandes, A. M.; Sobrinho, JSP; de Souza, F. P.; Villa, L. L.; Rahal, Paula [UNESP] (Wiley-Blackwell, 2006)
Oncogenic human papillomavirus (HPV), a causative agent of uterine cervical cancer, has also been detected in head and neck squamous cell cancers, especially in squamous cell carcinomas of the tonsils. However, the true HPV prevalence in normal and neoplasic oropharyngeal mucosa remains uncertain. To determine the prevalence of HPV DNA in normal oropharyngeal mucosa of cancer-free individuals, a study was carried out on 50 Brazilian subjects. PCR was performed to identify HPV DNA in samples from four sites in the oropharynx (tonsils, soft palate, base of the tongue, and back wall of the pharynx). For amplification of the HPV DNA, MY09/11 consensus primerswere used, and specific genotypes were identified by dot-blot hybridization or cloning and sequencing. HPV DNA was present in 14.0% of the individuals, and the identified genotypes were 16, 18, 52, and 61. All these types are considered high-risk (HR) HPV. The tonsils and the soft palate were the sites with the highest HPV prevalence. This study shows the prevalence of HR HPV in the oropharynx of normal individuals. However, the prevalence of HPV is still unclear, and if HPV infection in a healthy it is not known individual predisposes to HPV-associated disease such as oropharyngeal cancer. Thus, it is important to assess the prevalence of HPV in cancer-free individuals, in order to compare it with the HPV prevalence in oropharyngeal carcinomas and to attempt to determine the true role of HPV in the development of head and neck squamous cell cancers. (c) 2006 Wiley-Liss, Inc.
Keywords: HPV; head and neck squamous cell cancers; cancer-free individuals; oropharynx